Empirical Evaluation of Decentralized Genomic Data Computation Using Bacalhau and IPFS - Triaji, Bagas; Badiyanto, Badiyanto; Afif, Justivan Intifadhah (Asosiasi Doktor Sistem Informasi Indonesia, 2025)
Large-scale genomic analysis typically relies on centralized infrastructures, creating conflicts between collaborative needs and data sovereignty regulations. This study solves this dilemma by evaluating a decentralized architecture designed to facilitate secure, inter-institutional genomic computation without moving raw data. We integrated Bacalhau for orchestration and IPFS Cluster with CRDT consensus for storage, employing AES-256 encryption. A quantitative evaluation was conducted on AWS using five t3.medium nodes to simulate a resource-constrained hospital network. We tested three scenarios: a centralized baseline (SSH+SCP), an ideal decentralized workflow, and a